2001
DOI: 10.1210/jcem.86.8.7727
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Myofilament Proteins and Decreased cGMP-Dependent Protein Kinase in the Human Uterus during Pregnancy

Abstract: Excessive or premature contractions of uterine smooth muscle may contribute to preterm labor. Contractile stimuli induce myosin and actin filament interactions through calcium-dependent myosin phosphorylation. The mechanisms that maintain myometrial quiescence until term are not well established, but may include control of calcium levels by nitric oxide and cGMP signaling and thin filament (caldesmon and calponin) regulation. Previously, we reported that myometrial tissues from pregnant rats are not responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…This is consistent with that previously reported for both human and rat myometrium [22,27,32]. h-Caldesmon is a thin filament-associated protein that inhibits actomyosin MgATPase activity [33].…”
Section: Expression Of Caveolin-1 -2 Rok Mlc 20 and H-caldesmon Insupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with that previously reported for both human and rat myometrium [22,27,32]. h-Caldesmon is a thin filament-associated protein that inhibits actomyosin MgATPase activity [33].…”
Section: Expression Of Caveolin-1 -2 Rok Mlc 20 and H-caldesmon Insupporting
confidence: 92%
“…There is an emerging body of evidence suggesting that human pregnancy, and labour onset, is associated with translational changes in many molecules whose main influence is to limit uterine activity [22,23,[34][35][36]. As ROKα and MLC 20 are key proteins implicated in smooth muscle contractile activation, their decreased expression with pregnancy reported here, coupled with an enhanced expression of h-caldesmon, may also contribute to this adaptive situation before parturition.…”
Section: Physiological Significance Of the Findingsmentioning
confidence: 62%
See 1 more Smart Citation
“…Others, including calponin and h-caldesmon, modulate the actomyosin complex (13,14). Previous studies have shown that expression levels of contractile apparatus proteins increase with pregnancy (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…One postulated mechanism is that NO increases cGMP and relaxes smooth muscles via the inhibition of myosin light chain phosphorylation (Buxton, 2008;Cornwell et al, 2001). Another possible mechanism is that increased cGMP levels lead to hyperpolarisation of the cellular membranes ( (Khan et al, 2009;Zygmunt and Hogestatt, 1996) resulting in smooth muscle relaxation.…”
Section: Discussionmentioning
confidence: 99%